Situation Report: Romania, 21 January 1966 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Ceausescu Receives Soviet Embassy Counsellor Romanian-Yugoslav Trade Talks New Ambassador to North Korea Romanians to Inspect British Nuclear Power Plant Celebration of the Union of Principalities